Empirical model simulating rainwater harvesting system in Tropical area - Mohammed, Thamer Ahmed; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
Rainwater harvesting is the technique of capturing the rainfall to meet some water needs in both urban and rural areas. The volume of rainwater collected from rainwater harvesting system varies from place to place and depends mainly on the climatic condition. Typically, the rainwater harvesting system is composed of the catchment (roof), gutter, rainwater pipe, and storage tank. Reliability of a rainwater harvesting system mainly depends on the collected volume in rainwater storage tank and it is also used to check whether the collected volume of rainwater can meet a specific water demand (either for potable or non-potable uses).